Family History and Historians in Australia and New Zealand
1 online resource (216 pages
Keywords: Since the turn of the twenty-first century, family history is the place where two great oceans of research are meeting: family historians outside the academy, with traditionally trained, often university-employed historians. This collection is both a testament to dialogue and an analysis of the dynamics of recent family history that derives from the confluence of professional historians with family historians, their common causes and conversations. It brings together leading and emerging Australian and New Zealand scholars to consider the relationship between family history and the discipline of history, and the potential of family history to extend the scope of historical inquiry, even to revitalise the discipline. In Anglo-Western culture, the roots of the discipline's professionalisation lay in efforts to reconstruct history as objective knowledge, to extend its subject matter and to enlarge the scale of historical enquiry. Family history, almost by definition, is often inescapably personal and localised. How, then, have historians responded to this resurgence of interest in the personal and the local, and how has it influenced the thought and practice of historical enquiry?